Investment Decisions and the Equity Accounting Standard. - Comiskey, Eugene E.; Mulford, Charles W. (The Accounting Review, 1986)
Abstract ABSTRACT: This study tests the proposition that the 20 percent ownership percentage criterion for application of the equity method influences firm investment decisions. A sample distribution of firm investment positions indicates an unusually heavy concentration of positions at or near 20 percent. The characteristics of 19 to 19.99 percent investees (carried at cost) are then contrasted with 20 to 20.99 percent investees (carried at equity) on dimensions of profitability and earnings covariability. The results suggest that the extent-of-holding dimension of firm investment decisions is influenced by the ownership criterion. This finding implies that the underlying standard (APB 18) has an economic consequence. This result should be of interest to accounting scholars, as well as of potential value to the FASB as it reconsiders accounting standards for consolidations and the equity method.